2015
DOI: 10.1186/s40795-015-0020-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of plasma lipid profile by lactobacillus fermentum (probiotic strain ME-3 DSM14241) in a randomised controlled trial of clinically healthy adults

Abstract: Background: Previous studies showed that a probiotic-rich diet may improve the plasma lipid profile and lower the risk of cardiovascular disease (CVD). In a randomized controlled study we tested the possibility for regulation of plasma lipid profile using a kefir that contained the antioxidative probiotic strain, Lactobacillus fermentum ME-3 (DSM14241). The trial was performed in clinically healthy adults with borderline-high serum low-density lipoproteincholesterol (LDL-C) and/or high serum triglyceride (TG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Our previous data from 8 weeks versus data from 4 weeks showed that consumption of LFME3 enriched kefir, but not the placebo kefir, significantly decreased the level of LDL cholesterol [34]. Next, only the probiotic kefir in 8 weeks decreased significantly the ratio of TG/HDL cholesterol.…”
Section: Discussionmentioning
confidence: 93%
“…Our previous data from 8 weeks versus data from 4 weeks showed that consumption of LFME3 enriched kefir, but not the placebo kefir, significantly decreased the level of LDL cholesterol [34]. Next, only the probiotic kefir in 8 weeks decreased significantly the ratio of TG/HDL cholesterol.…”
Section: Discussionmentioning
confidence: 93%
“…through epigenetic reprogramming (Shenderov, 2014). In addition, there is a high heterogeneity in the metabolic properties among species and bacterial strains (Mikelsaar et al, 2015). However, most LAB require an exogenous nitrogen source of amino acids or peptides to support cell growth (Manca de Nadra, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…L. fermentum is usually found in habitats that are nutrient rich and are associated with humans, plants, animals, and food ( 2 ). L. fermentum is considered a promising potential probiotic candidate due to its lack of antibiotic resistance genes, along with its antioxidative, antimicrobial, and cholesterol reduction properties ( 3 5 ). The genome of L. fermentum possesses specific genes that help it to tolerate the immune system of the host, interact with the other microbes of the gut, and colonize the host epithelium ( 6 8 ).…”
Section: Announcementmentioning
confidence: 99%